The Effect of Using Earphones on the Improvement of TOEFL Listening Comprehension Scores among Second-Semester Students of the Faculty of Agriculture at Universitas Indonesia Timur - Suci Ayu; Rusliana; Joko Purwanto; Munaing (Public Resource Innovation Management and Excellence, 2025)
This study aims to examine the effect of using earphones on improving students’ TOEFL listening comprehension performance. The research employed a quasi-experimental design with two groups: an experimental group using earphones and a control group without earphones. A total of 60 students participated in the study, with 30 students assigned to each group. The research instrument was a TOEFL Listening test administered in both pre-test and post-test sessions. The findings revealed a significant improvement in the experimental group’s scores. The average TOEFL Listening score in the earphone group increased from 420 in the pre-test to 470 in the post-test (+50 points). In contrast, the control group’s average score improved only from 415 in the pre-test to 430 in the post-test (+15 points). These results indicate that the use of earphones can enhance students’ concentration and comprehension during listening tasks, which in turn positively affects their TOEFL Listening outcomes. This study highlights the need for further investigation, as listening comprehension performance is not solely determined by supportive devices such as earphones but also by internal factors, including students’ language proficiency, listening strategies, and concentration levels during the test. Accordingly, this research contributes to a deeper understanding of the factors influencing students’ success in TOEFL, particularly in the listening comprehension section.